Contribution to studies on the impact of marine pollution on groundwater quality in the islands - Sylla, Mamadouba; Diallo, Moussa; Keita, Kandas; Bah, Alpha Oumar (International journal of innovation and applied studies, 2025)
This review, based on the impacts of marine pollution on groundwater quality in the islands, provides ample evidence of the complexity of the socio-economic and environmental management of the islands due to their geographical position and human pressure. The coastal ecosystem of the islands is complex, dynamic and, above all, vulnerable to human activity, marine intrusion and climate change. In addition, it can come from a variety of sources such as agriculture, industry, tourism, inadequate waste management and mining activities. It is essential for these island communities to implement effective measures to prevent groundwater pollution and protect their precious water resources. The aim of this study was to review the literature on the impact of marine pollution on groundwater quality in island regions. The aim was to identify all the parameters influencing groundwater pollution on islands.